Impact Of Ship Service On Timeliness Of Payment (Disbursement) At Terminals for Self-Interest At PT Pertamina International Shipping - Ghina, Devita; Kusumawati, Elly; Damanik, Antony; Sianturi , Intan (Politeknik Ilmu Pelayaran Semarang, 2024)
The purpose of this study was to determine how the handling of the flow of ship service related to payment (disbursement) accompanied by its documents and to determine the impact of ship service on the timeliness of payment (disbursement). This study uses a survey method with a descriptive quantitative analysis approach. Data collection techniques are carried out by observation, distributing questionnaires in the form of a Likert scale, interviews, documentation, and literature studies. Primary data in the form of questionnaires obtained from 30 respondents and interviews obtained from 4 respondents. Secondary data in the form of observation and documentation. The population in the questionnaire was 30 respondents and used a saturated sample where the sample was based on the existing population. The data management tool in this study used SPSS for windows ver. 26. Based on the results of valid questionnaires and interviews, this study shows that handling the flow of ship service according to procedures will increase the timeliness of payment (disbursement) and ship service has an impact of 58.3% on the timeliness of payment (disbursement). Thus, there are still delays in issuing invoices and services provided as identified through analysis of aspects of tangible evidence, reliability, responsiveness, assurance, and empathy.